STREET FOOD: ASSESSING ITS IMPACT ON PUBLIC HEALTH, ECONOMY, AND SOCIETY IN LIGHT OF NUTRITIONAL BENEFITS AND MICROBIAL RISKS – A NARRATIVE REVIEW - Gonçalves, Bruna Vilarinho; da Silva, Beatriz Virgínia; Andrade, Anderson Assunção (Acta Biologica Brasiliensia, 2024)
Street food serves as a global culinary phenomenon, reflecting cultural diversity and enriching tourism experiences. However, concerns arise regarding its safety due to microbial contamination, posing significant public health risks. This narrative review assesses the interplay between street food, public health, economy, and society. It explores microbial risks, emphasizing deficient hygiene practices among vendors and inadequate infrastructure. Despite nutritional benefits, street food consumption contributes to foodborne diseases, disproportionately affecting vulnerable populations, especially in low- and middle-income countries. Moreover, street food vendors, predominantly women in developing nations, face socioeconomic challenges despite their crucial role in the economy. Legalizing and regulating street food operations are imperative for enhancing food safety, supporting livelihoods, and fostering socioeconomic empowerment. Overall, understanding and addressing the multifaceted impact of street food are essential for promoting public health and sustainable development.